Corporate obligations under international law - Karavias, Markos (Oxford : Oxford University Press, 2014)
The international legal status of corporations is a contentious issue, as they do not easily fit within a system traditionally designed around states. This book assesses the ways in which corporations are bound by international human rights and environmental law, and the form their obligations take.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on January 6, 2014).
Keywords: Corporation law; International law; Human rights; Environmental law